The psychology of work insights into successful working practices - Gautier, Chantal (London Philadelphia Kogan Page, 2015)
"Work engagement is an intriguing dimension of workplace psychology. According to a study done by Gallup, 87% of employees identify as either not engaged or actively disengaged, and actively disengaged employees currently outnumber engaged employees 2-to-1.To make sense of people's behavior in complex organizations, instead of offering a dry presentation of organizational psychology theories, Chantal Gautier analyzes transcripts from interviews with people at different levels in various types of organizations and sheds light into real organizational work practices. Personal narratives, exercises and reflective practices make the material relatable to everybody's experience.The Psychology of Work explores the role of integrity, recognition, commitment, leadership, communication, and autonomy in employee engagement and happiness. It raises awareness of current working practices and stresses the need for change. Offering very practical advice, Gautier emphasizes the importance of putting the "humane" back into organizational life. "-- Provided by publisher.
"The Psychology of Work integrates psychological theory with personal narrative from global industry leaders, as well as those entering the workforce, to offer tangible insights into the real world of work. It is ideal for students, professionals and anyone with an interest in how successful organizations operate. It charts the development of the field of organizational psychology and provides the key theoretical frameworks. Crucially, it explores how these can be utilised to enhance organizational culture, and why this is so relevant and important in the modern workplace. Through the inclusion of interviews with students, The Psychology of Work reveals what the future workforce expect of the organizations that they are going in to and encourages students reading the book to reflect on what kind of leaders they would like to be. The book is also a valuable resource to support professionals and practitioners, highlighting current working practices and the need for change, offering practical guidance on how to bring the 'humane' back into organizational life"-- Provided by publisher.
Includes bibliographical references (pages 177-193) and index.
Keywords: Work -- Psychological aspects; Psychology, Industrial; Corporate culture; Employee motivation